Our eyes for life : a health communication campaign that aims to encourage regular eye screening behaviour among Singaporeans aged 40 to 60 - Chan, Shu Hui (2018)
Our Eyes for Life is an integrated health communication campaign by four final year undergraduates from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. The campaign encouraged Singaporeans aged 40 to 60 years old to attend eye screenings and ran in Tampines Group Representation Constituency. This paper outlines primary and secondary research about Singapore’s eye health landscape. Guided by communication theories and relying on research insights, Our Eyes for Life aimed to raise awareness about Singapore’s four common age-related eye diseases, and increase perceived susceptibility towards these eye diseases, level of subjective norms and behavioural intentions to attend eye screenings. Key strategies included utilising eye health professionals as campaign experts, tapping on community touch points in Tampines, such as grassroots leaders and places of worship, and positioning Tampines residents who have eye diseases as eye health advocates. Some key tactics were the creation of a WhatsApp subscription service, producing videos featuring eye health experts and using virtual reality and simulation glasses to demonstrate the effects of eye diseases. The campaign was evaluated through analysing post- campaign survey results and measuring our impact and output objectives. The campaign may have influenced subjective norms and achieved most output objectives. Lastly, this paper discusses strengths and limitations of the campaign, concluding with future directions and sustainability, where the campaign will be replicated in another part of Singapore. Original documents, including campaign collaterals, event photography, email correspondences and relevant data, are included in the appendices as references to the main paper.